Higher specialist training in accident and emergency medicine--past, present and future. Issue 2 (March 1997) - Johnson, G; Brown, R; Howell, M
Abstract : OBJECTIVE: To assess the quality of accident and emergency (A&E) medicine higher specialist training as perceived by current trainees and those who have recently completed training. METHODS: Postal questionnaires to three groups of A&E specialists either currently in training or having recently completed training. RESULTS: Levels of satisfaction were generally high. Previously identified deficiencies in management training remained and the implementation of guidelines regarding formative assessment and time for study and research was inconsistent. CONCLUSIONS: While clinical training is largely satisfactory, areas where higher specialist training could be improved have been identified. Continued development is necessary to meet the challenges of the new specialist registrar grade and opportunities and threats to training in the future are proposed and discussed.